PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN SARIO KOTA MANADO - SAMUEL NELWAN TARANDUNG; ARIE RORONG; FEMMY TULUSAN (Sam Ratulangi University, 2022)
The purpose of this study was to determine the application of the principles of good governance in improvingthe quality of public services in the Sario District Office, Manado City. This research uses descriptivequalitative research. Sources of data used in this study are primary data and secondary data with datacollection techniques namely observation, interviews and documentation. The theory used is the theory ofSedarmayanti (2012) which states that good governance is a government that requires the commitment andinvolvement of all parties, namely the government, society, so that good government can become a realityand run well. This study uses indicators namely: Responsiveness, Effectiveness and Efficiency, Fairness,and Accountability, and Transparency. Based on the results of the study, it shows that the application of theprinciples of good governance in improving the quality of public services at the Sario sub-district office,Manado City, has not run optimally. This is related to the obstacles seen from the aspects of Responsiveness,Effectiveness and Efficiency, Fairness and Accountability, and Transparency.Keywords: Good Governance, Public Services